Blastocystis: Emerging Protozoan Parasite with High Prevalence in Iran - Badparva, Ebrahim; Fallahi, Shirzad; Arab-Mazar, Zahra (Novelty in Biomedicine, 2015)
Background: Blastocystis is a zoonotic protozoan parasite habit in intestinal tract of humans and wide range of animals. Because of the mysterious nature and unknown or less-known aspects of Blastocystis, comprehensive information about epidemiology of this parasite is not available. The objective of this study was to investigate the available parasitology studies during the last decade in Iran and determine the prevalence of Blastocystis and its position among other intestinal parasites. As well as, investigate the effective factors in its prevalence. Materials and Methods: All available studies related to the prevalence of intestinal parasites in Iran during the recent decade were collected using information databases. After determinant the mean prevalence of each parasite, the most common parasites, and effective factors on their prevalence were assessed and analyzed. Results: Different studies showed that the most common intestinal parasite at this period of time was Blastocystis spp. with 14.6% prevalence rate. Additionally, in 44.5% of cases Blastocystis spp. allocated the first and in 100% of cases, the first to third rank of the most common intestinal parasites in Iran. Giardia lamblia and Entamoeba coli were in the next category. Conclusion: To our knowledge, the present study is the first survey in which the Blastocystis spp. introduces as one of the most common intestinal parasites in human. Various factors, including the low sensitivity of routine diagnostic methods, hosts multiplicity, easy transportation and unknown impressive factors are effective in the increased prevalence of this parasite. The results of this study could improve the attitude of teachers and researchers towards Blastocystis spp.